Telecommunications for nurses : providing successful distance education and telehealth - Armstrong, Myrna L.; Frueh, Shari (Springer Pub., 2003)
"It is a book which describes how creative people, often taking a fresh approach, can get the best out of what modern distance communications technology has to offer."--The foreword by Susan M. Sparks, RN, PhD, FAAN, Senior Education Specialist, National Library of Medicine. This book reflects recent developments in both distance education and telehealth, focusing on practical strategies nurses can put to use in the classroom or clinic. Each chapter is written by acknowledged experts for the particular topic. The previous edition won an American Journal of Nursing Book of the Y